2018
DOI: 10.24106/kefdergi.3185
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on Turkish EFL Majoring Students’ Unethical Behaviors

Abstract: Birçok bilimsel çalışma aşırmacılık konusunu farklı eğitim bağlamlarında araştırmıştır. Ancak, çok az sayıda araştırma yabancı dil olarak İngilizce öğrenen Türk öğrencilerin etik anlayışını cinsiyet ve izlenim yönetimi perspektiflerinden araştırmıştır. Verilerin toplanması için akademik aldatma ölçeği, izlenim yönetimi ölçeği ve kişisel nitelikler anketi kullanılmıştır. Bu araştırma, İngilizceyi yabancı dil olarak öğrenen Türk öğrencilerinin akademik davranışlara, izlenim yönetimine ve psikolojik cinsiyete yön… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The second is to investigate the variables that best explain the academic dishonesty tendency levels of the students who continue their graduate education by using the CHAID (Chi-squared Automatic Interaction Detection) analysis method. When the literature is examined (Adıbatmaz & Kurnaz, 2017;Akbaşlı et al, 2019;Akdağ & Güneş, 2002;Ayoub/Al-Salim & Aladwan, 2021;Barın et al, 2018;Bateman & Valentine, 2010;Belet-Boyacı et al, 2017;Brown, Bourke-Taylor et al, 2019;Brown, Isbel et al, 2020;Burns, et al, 1998;Chow et al, 2021;Coate & Frey, 2000;Çenberci, 2018;Çetin, 2007;Dağaşan et al, 2017;Dam, 2013;Demir & Arcagök, 2013;Duran, 2020;Eminoğlu-Küçüktepe & Küçüktepe, 2012;Eriksson & McGee, 2015;Ersoy & Özden, 2011;Gümüşgül et al, 2013;Hadjar, 2019;Hensley et al, 2013;Kadı et al, 2016;Kaymakcan, 2002;Keçeci et al, 2011;Kıral & Saracaloğlu, 2018;Kocaman-Karoğlu & Bakar-Çörez, 2020;Koç, 2018;Korn & Davidovitch, 2016;Lin & Wen, 2007;McCabe & Trevino, 1997;Nonis & Swift, 1998;Novianti, 2022;Ömür et al, 2014;Öztürk-Başpınar & Çakıroğlu, 2019;Özyurt & Eren, 2014;…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The second is to investigate the variables that best explain the academic dishonesty tendency levels of the students who continue their graduate education by using the CHAID (Chi-squared Automatic Interaction Detection) analysis method. When the literature is examined (Adıbatmaz & Kurnaz, 2017;Akbaşlı et al, 2019;Akdağ & Güneş, 2002;Ayoub/Al-Salim & Aladwan, 2021;Barın et al, 2018;Bateman & Valentine, 2010;Belet-Boyacı et al, 2017;Brown, Bourke-Taylor et al, 2019;Brown, Isbel et al, 2020;Burns, et al, 1998;Chow et al, 2021;Coate & Frey, 2000;Çenberci, 2018;Çetin, 2007;Dağaşan et al, 2017;Dam, 2013;Demir & Arcagök, 2013;Duran, 2020;Eminoğlu-Küçüktepe & Küçüktepe, 2012;Eriksson & McGee, 2015;Ersoy & Özden, 2011;Gümüşgül et al, 2013;Hadjar, 2019;Hensley et al, 2013;Kadı et al, 2016;Kaymakcan, 2002;Keçeci et al, 2011;Kıral & Saracaloğlu, 2018;Kocaman-Karoğlu & Bakar-Çörez, 2020;Koç, 2018;Korn & Davidovitch, 2016;Lin & Wen, 2007;McCabe & Trevino, 1997;Nonis & Swift, 1998;Novianti, 2022;Ömür et al, 2014;Öztürk-Başpınar & Çakıroğlu, 2019;Özyurt & Eren, 2014;…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…On the other hand, when students' frequency of cheating according to gender was examined in the literature, it was observed that females come to the fore in terms of rarely cheating and that males come to the fore in terms of cheating more frequently (Duran, 2020). In addition, there are studies not reporting significant differences between males and females in terms of their cheating tendencies (Ayoub/Al-Salim & Aladwan, 2021;Barın et al, 2018;Çenberci, 2018;Çetin, 2007;Dam, 2013;Keçeci et al, 2011;Lin & Wen, 2007;Novianti, 2022;Pearson, 2019;Szabo & Underwood, 2004;Tümkaya, 2019;Ünlü & Eroğlu, 2012).…”
mentioning
confidence: 99%